1986
DOI: 10.1152/jappl.1986.61.2.530
|View full text |Cite
|
Sign up to set email alerts
|

Differences in regional vascular conductances in isolated dog lungs

Abstract: The distribution of pulmonary blood flow is influenced by gravity, regional lung expansion, and hypoxic pulmonary vasoconstriction. However, these factors cannot completely explain the three-dimensional distribution of blood flow in the lung. The present study was designed to see whether anatomically related factors could contribute. Regional blood pressure vs. flow curves were determined in 100-230 small parenchymal samples (0.3-0.4 ml) from 12 isolated perfused dog lungs held at constant inflation pressure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
67
2
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(82 citation statements)
references
References 0 publications
11
67
2
1
Order By: Relevance
“…The observation that substantial perfusion was preserved in dorsal lung regions in the prone position is consistent with previous observations in oleic acid-induced lung injury (3,24,25) and in healthy animals (26)(27)(28)(29)(30), and it could be due to higher vascular conductance in these regions (31,32). However, the fact that the vertical perfusion gradient was not fully reversed in the prone position suggests some degree of perfusion redistribution toward ventral regions, consistent with results obtained in oleic acidinduced lung injury (25).…”
Section: Effect Of the Prone Position On Regional Perfusion Shunt Asupporting
confidence: 92%
“…The observation that substantial perfusion was preserved in dorsal lung regions in the prone position is consistent with previous observations in oleic acid-induced lung injury (3,24,25) and in healthy animals (26)(27)(28)(29)(30), and it could be due to higher vascular conductance in these regions (31,32). However, the fact that the vertical perfusion gradient was not fully reversed in the prone position suggests some degree of perfusion redistribution toward ventral regions, consistent with results obtained in oleic acidinduced lung injury (25).…”
Section: Effect Of the Prone Position On Regional Perfusion Shunt Asupporting
confidence: 92%
“…Posturemediated changes were primarily oriented along the ventrodorsal axis for blood flow, as seen in CT studies (8,17,29). The finding of our study that substantial perfusion was preserved in dorsal lung regions in the prone position is consistent with previous observations in healthy large animals (2,4,15,36,39). The gravitational gradient was different in the supine and prone positions according to a PET study in dogs (36), contrary to PET measurements in humans (23).…”
Section: Body Position and Pbfsupporting
confidence: 91%
“…The use of a dedicated small animal PET could allow this method to be translated to rodents. Therefore, we tested the feasibility of measuring PBF in rats using biodegradable, 68 Ga-radiolabeled human serum microspheres (Ga-68-microspheres) and micro-PET.Subsequently, and with a variety of radiotracers, positional changes in regional blood flow from upper to lower regions have been found in large animals and humans (4,15,23,25,33,36). However, to the best of our knowledge there are no data regarding the influence of posture (prone and supine) on regional pulmonary blood flow in small animals.…”
mentioning
confidence: 99%
“…In the lung NO is formed in both the airway and in the vasculature. Beck and Rehder (Beck and Rehder, 1986) showed that vascular conductance was higher in dorsal lung in dogs in the supine, lateral and head-up positions, but the prone position was not examined. Evidence for uneven formation of NO in the lung was provided by in vitro studies showing greater eNOS activity in dorsal than in ventral lung regions in animals and humans, and similar regional differences in NO-mediated vasorelaxation in equine and porcine pulmonary arteries (Pelletier et al, 1998, Rimeika 2004et al, Rimeika et al, 2006.…”
Section: Endogenous No and V/q Matching Paper Iv: Inhibition Of Constmentioning
confidence: 98%